PENGARUH INDEPENDENSI AUDITOR PADA KAP BIG FOUR TERHADAP MANAJEMEN LABA PADA INDUSTRI BAHAN DASAR, KIMIA DAN INDUSTRI BARANG KONSUMSI - NINI NINI; ESTRALITA TRISNAWATI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2009)
This research examine the effect of professional ethics, audit fee, and non audit services to earnings management at Basic-Chemical and Consumer Good Industries that are listed in BEI. Samples are obtained by purposive sampling method and obtained 17 observation data from 2004-2008. The result indicate that professional ethics and non service audit are significantly affect the earnings management.